KEBEBASAN MAHASISWA DALAM BERPENDAPAT DARI PRESPEKTIF HAM - Qudsya, Amalia Laila; Habibah, Siti Maizul (Gapenas Publisher, 2023)
From a human rights standpoint, students' fundamental right to free speech is protected by the state constitution and fundamental laws. For students to be able to express their opinions without fear of retaliation or intimidation, they must have the fundamental right to freedom of expression. The state's basic laws and the constitution both safeguard the right to freedom of expression from the perspective of human rights. Of course, there are limitations on the right to free speech that must be observed, such as the requirement to respect the legal system and the human rights of others. The 1945 Constitution's Article 28E, paragraph (3), which states that